THE LEVEL OF EFFECTIVENESS OF ONLINE LEARNING AT THE ELEMENTARY SCHOOL (SD) LEVEL - Desiono, Maula; Masdiana, Masdiana; Irawan, Dedi (JLCEdu (Journal of Learning and Character Education), 2022)
Online learning serves as a lesson between educators and students by using an internet network that can be accessed anytime and anywhere. Of course, the online method has a good level of effectiveness if it can be implemented optimally but also vice versa if there are still many obstacles in the implementation poses, it will also cause several problems whose consequences will have an impact or be felt by educators and students in the school. This time the author will conduct a study carried out at Sribasuki State Elementary School 1, Kalirejo District, Central Lampung Regency about the implementation of online learning at the school. The purpose of this study is to determine the level of effectiveness of online learning at the elementary school level. The method collected in data collection is a question and answer (interview) to the resource persons, namely several students, parents of students, and educators (teachers) directly or via WhatsApp. The results of the study showed various opinions from students, parents, and educators (teachers). From these various opinions, it can be concluded that the online method is very helpful in the learning process and it is considered that the method is quite appropriate to be chosen during the current Covid-19 Pandemic, but on the other hand, the level of effectiveness is still assessed below the learning carried out face-to-face. Therefore, some students, parents, and educators (teachers) really hope that the learning process can be carried out face-to-face as soon as possible.